Effect of Post and Core Materials on Fracture Strength in the Crown Reconstruction of the Root-Treated Tooth - Sareh Habibzadeh; Mohammad Javad Kharazifard (Mashhad University of Medical Sciences, 2020)
Introduction: Root canal-treated teeth are more prone to failure in functional forces. Post and core procedures are often indicated in these cases. On the other hand, there have been interests in the use of all-ceramic restorations with improved properties in posterior teeth reconstruction. This study aimed to investigate the fracture strength of four different post and core systems in root canal-treated premolars with all-ceramic crowns. Materials and Methods: A total of 48 mandibular premolars were selected and subjected to root canal standard treatment. Afterward, they were divided into four groups of Ni-Cr post and cores casting, glass fiber post/composite core, non-precious gold post and cores casting, and custom-made milled zirconia posts and cores. Each specimen received all-ceramic crowns with zirconia copings and was then loaded by the Zwick device. The amount of fracture resistance by the specimens up to the breaking point was measured and the modes of failure were analyzed in this study. The data were analyzed using analysis of variance and Tukey's honest significance test (α=0.05). Results: The mean fracture strengths of the four groups were 780.59±270, 70±323, 963.24±915.307, and 435.34±220 N, respectively. There were differences between the core and post groups regarding this difference (P=0.000). Conclusion: According to the results, out of the post-and-core procedures used for the reconstruction of prosthetic root canal-treated premolars with all-ceramic crown, the custom-milled zirconia had lower fracture strength, and non-restorable fractures were more prevalent in these posts.